Eyes on you a comparative critical discourse analysis of the portrayal of the Metro Manila urban poor through images and captions in major Philippines newspapers under the Estrada, Arroyo, Aquino and Duterte administrations - Cabel, Inna Christine Reyes; Endona, Gabrielle Anne S.; David-Cancio, Kara Patria C. (2018)
"Over the past few decades, the urban poor have come to dominate public images of poverty. Media coverage and discussions involving government intervention and public policy have generated internal divisions, such as the perceived notion of the "deserving" and "undeserving" poor. This study explores the media's framing of the urban poor and its relationship with the dominant idea of the poor perpetuated in society. Critical discourse analysis and the theory of visual semiotics was used by the researchers. The study analyzed images and captions from two major broadsheets, Philippine Daily Inquirer and Philippine Star, to prove that the media does have a role in cultivating its audience's view of the urban poor. Along with this, the study identified significant differences between each administration's poverty programs, and how this has been communicated to the public by the media through images of the urban poor. In considering the socio-political context in which the photos were taken, the researchers have found that media coverage of the urban poor portrayed issues of poverty as confined to the problems each administrations's flagship poverty program centers on. Apart from this, results have shown that the photos and captions feed the public with the image that the urban poor continue to be lazy, irresponsible and "undeserving", without giving context as to why they are in their current conditions."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Urban poor -- Philippines -- Manila metropolitan area